Maximum power point controller for large-scale photovoltaic power plants using central inverters under partial shading conditions - Karanayil, Baburaj (2020)
The central inverter topology based on three-level converters is widely used in large-scale photovoltaic (PV) power plants because of its simple and reliable structure and high efficiency. However, when two PV arrays are connected in series for higher dc-link voltage, the single maximum power point tracking (MPPT) operation cannot function properly when there is partial shading between the arrays. This paper presents a configuration where the two PV arrays are connected in series together with an auxiliary power converter feeding a neutral-point-clamped central inverter. This configuration ensures maximum power production from both PV arrays during partial shading conditions, achieving the MPPT operation for both PV arrays. The proposed converter together with their controls are verified by simulation and experiment.